Antenatal depressed mood and child cognitive and physical growth at 18-months in South Africa: a cluster randomised controlled trial of home visiting by community health workers. (13th June 2017) - Tomlinson, M.; Rotheram-Borus, M. J.; Scheffler, A.; le Roux, I.
Abstract : Aim: To examine the child outcomes at 18-months post-birth of a population cohort of women with antenatal depressed mood, half of whom were randomly chosen to receive perinatal home visits from community health workers during pregnancy. Method: Pregnant women in 24 neighbourhoods (98% participation) were randomised by neighbourhood to: (1) standard clinic care (SC; 12 neighbourhoods; n = 594) or (2) the Philani Intervention Program, a home visiting intervention plus standard care (12 neighbourhoods; n = 644). The physical and cognitive outcomes of children of mothers with antenatally depressed mood (Edinburg Perinatal Depression Scale >13) in the intervention condition were compared at 18-months post-birth to children of mothers without depressed mood in pregnancy in both conditions. Results: More than a third of mothers had heightened levels of antenatal depressed mood (35%), similar across conditions. Antenatal depressed mood was significantly associated with being a mother living with HIV, using alcohol and food insecurity. At 18-months, the overall cognitive and motor scale scores on the Bayley Scales of Development were similar. However, 10.3% fewer children of mothers with antenatal depressed mood in the intervention condition had cognitive scores on the Bayley Scales that were less than 85 (i.e., s.d. = 2 lower than normal) compared with children of mothers with antenatal depressed mood in the SC condition. Intervention children of mothers with antenatal depressed mood were also significantly less likely to be undernourished (Weight-for-Age Z-scores < −2). Conclusion: Cognitive development and child growth among children born to mothers with antenatal depressed mood can be improved by mentor mother home visitors, probably resulting from better parenting and care received early in life.